Research on the deformation mechanism of reconfigurable wheel-tracked wheel with planetary expansion and retraction - LIU Jinfu; LI Zelin; XU Linsen; JIANG Zhengyan; SHEN Penghui (Jixie chuandong, 2025)
ObjectiveTo meet the task requirements of ground-based special robots in complex environments, such as earthquake relief, a wheel-tracked reconfigurable wheel without elastic compensation elements was designed.MethodsFirstly, the system composition and working principles of the planetary expansion and retraction mechanism, deformation mechanism, and clutch mechanism were introduced, and the motion modes achievable by the deformable wheel in different working scenarios were discussed. Secondly, a geometric parameter model of the wheel deformation process was established, and the wheel-tracked transformation mechanism was analyzed. Factors affecting the length of the track before and after deformation,such as the rotation angle of the linkage, slider displacement, and central coordinates of the deformation mechanism were identified. Then, a prototype of the robot and a test platform were designed, and the test validation was conducted. Finally, a control system was developed, and the wheel’s speed and passability were tested in three environments: flat ground, muddy terrain, and sandy terrain.ResultsThe results show that the length variation rate of the track in wheel and track modes is only 0.29%. Through the coordinated action of the deformation mechanism, transmission mechanism and clutch mechanism, the deformable wheel can fully achieve switching among nine motion modes, providing reference for future multi-scenario applications of special robots.